Implementasi Karakter Kreatif dan Tanggung Jawab dalam Organisasi Mahasiswa(Studi Kasus pada Himpunan Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar Periode 2016/2017) - Setyawan, Anulat Budi; , Honest Ummi Kaltsum, S.S., M.Hum (2017)
Abstract This study is aimed at 1) Describing implementation creative character in student organization, 2) Describing implementation responsibility in student organization. The study was conducted by using qualitative research. In triangulasi (collecting data, the writer used interview, observation and documentation). Then, the technique of analyzing data used interactive model. The validity of data used triangulations of resource.This study shows that:Implementation creative character include(1) HMP PGSD can do new innovation, that is implementation training of debate, (2) Take a risk in permission of lecturer and public speaking, (3) They have highly curious and asking to senior. Implementation creative character include(1) Time management already is good, they consider to implementation activity program with their schedule of lecture, (2) implement job disk together as responsibility, (3) Crew of HMP PGSD already become a guide in uniform or dress appropriately, (4) Crew of HMP PGSD use discussion to problem solving. Key Words: creative, responsibility, student organization